1986
DOI: 10.1177/070674378603100107
|View full text |Cite
|
Sign up to set email alerts
|

Telepsychiatry: Psychiatric Consultation through two-way television. A controlled study.

Abstract: Telepsychiatry (consultation carried out through 2-way interactive television) has been the object of a number of trials in the past twenty years, but to our knowledge there is no previous control study which compares CCTV and face-to-face interviews. Various aspects of the interviews carried out on CCTV were rated on a 5-point scale in questionnaires filled out by: (a) patients; (b) consultees and; (c) consultants. No significant difference was elicited with control interviews in respect to patients' diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
80
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(88 citation statements)
references
References 5 publications
7
80
0
1
Order By: Relevance
“…Our findings showed that patients were satisfied with the doctor-patient communication in telemedicine consultations, and this finding is consistent with other studies (9,10). In respect of the patient satisfaction level, Hall and Doran (17) showed that patients routinely reported high levels of satisfaction with the care received.…”
Section: Patient and Doctor Satisfaction Itemssupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings showed that patients were satisfied with the doctor-patient communication in telemedicine consultations, and this finding is consistent with other studies (9,10). In respect of the patient satisfaction level, Hall and Doran (17) showed that patients routinely reported high levels of satisfaction with the care received.…”
Section: Patient and Doctor Satisfaction Itemssupporting
confidence: 92%
“…Previous studies (9,10) showed that there is no consensus as to whether telemedicine enhances or erodes the nature and content of doctor-patient communication. Ball et al (9) …”
Section: Advances In Telemedicine Technology Have Made It Possible Tomentioning
confidence: 99%
“…There are few studies on provider satisfaction with telepsychiatry. Provider satisfaction with telepsychiatry has had mixed reviews with some noting a positive experience and others noting problems with the process and quality of the interpersonal relationship [23,26]. Interestingly, rural providers had significantly higher satisfaction than suburban or urban providers.…”
Section: Applicationsmentioning
confidence: 98%
“…Overall patient satisfaction with telepsychiatry has been very high [7]. Several themes have emerged from the research studies including that most patients speak freely and rate the experience with the specialist positively [21]; patients prefer services with visual cues rather than telephone services alone [21]; and children [22,23], adolescents [24], adults [7], and geriatric patients [25] appear to be equally satisfied with telepsychiatry. There are few studies on provider satisfaction with telepsychiatry.…”
Section: Applicationsmentioning
confidence: 99%
“…This survey also found that the PDA, introduced in its current format only in 1996, is experiencing similarly rapid adoption, with more than one-half of MDs under age 35 years now using this technology. In contrast, only a limited number of telepsychiatry programs and telepsychiatrists are currently active within Canada, despite the fact that telepsychiatry in Canada was evaluated as early as 1986 (2). Why do the adoption rates vary for these innovative technologies-or, to restate the obvious, getting psychiatrists to adopt a new technology, even if it has apparently obvious advantages, may be attended by varying degrees of difficulty: why?…”
mentioning
confidence: 99%